(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Acute bronchiolitis is leading cause of hospitalization in infants below 2 years of age. Bronchiolitis being a viral disease, there is no effective treatment. 3% nebulized hypertonic saline and 0.9% nebulized normal saline are often used, although there is disagreement over their efficacy. The aim of this study was to evaluate the efficacy of 3% hypertonic saline in children with acute bronchiolitis in reducing clinical severity and length of hospital stay. Methodology: A randomized control trial carried out in the Department of Pediatrics, Dhaka Medical College Hospital from January 2013 to December 2013.Ninty children from 1 month to 2 years of age hospitalized with clinical bronchiolitis were randomized to receive 3% nebulized hypertonic saline(Group-I) or 0.9% nebulized normal saline (Group-II). Nebulization was done 8 hourly until discharge. Outcome variable were clinical severity score, duration of oxygen therapy and length of hospital stay. Results: Baseline clinical severity score and O2 saturation were in group-I 9.0±1.0 and 94.9±1.7 and in group- II 9.3±1.8 and 94.6±2.6 respectively (p>0.05). At 72 hours, the mean severity score for the group-I was 1.64±0.99 and that for the group-II was 3.0 ± 1.48 (95% CI -2.17 to - 0.53, p=0.002). The cases of group-I required a shorter duration of oxygen therapy compared to those of group-II (15.0±6.0 hours vs 26.4±5.37 hours, 95% CI -20.35 to -2.44, p<0.05). Forty two (93.3%) of the group-I children recovered by the end of72 hours and discharged whereas 26 (57.8%) of the group-II children recovered during the same period (p<0.05). Length of hospital stay was shorter in group-I compared to group-II (58.1±22.0 hours vs 74.7±27.2 hours, 95% CI -26.89 to- 6.17, p=0.002). None of the cases encountered any side-effects. Conclusion: Nebulization with 3% hypertonic saline significantly reduced clinical severity, length of hospital stay and duration of oxygen therapy in case of acute bronchiolitis in comparison to 0.9% normal saline and was safe. Bangladesh J Child Health 2018; VOL 42 (3) :130-137